Optimization the production profit of pabrik olahan bandeng Nirwana in Pati Regency using integer linear programming method with the solver assisted - Marfuah, Ismi; Dwijanto, Dwijanto (Universitas Negeri Semarang, 2021)
This research was aimed to get the total composition of each Bandeng-product that must be produced, so that it can maximize the profit of Pabrik Olahan Bandeng Nirwana. The data that was gotten in this research were the primary and the secondary data. The result of calculation showed the optimal profit to the amount of 2.451.847,00 IDR by producing 85 units of Rolade, 27 units of Nugget Bulat, 30 units of Nugget Stick, 20 units of Bakso, 25 units of Sempolan, 70 units of Sempolan Crispy, 40 units of Otak-otak and 62 units of Tahu Bakso. The ratio profit calculation using Integer Linear Programming compared with the calculation by Pabrik Olahan Bandeng Nirwana was up 190.106,00 IDR. The showed the profit gotten by Integer Linear Programming method had been optimal